Gamta (fragmentas) - Emerson, Ralph Waldo (Problemos, 2016)
Versta iš: Ralph Waldo Emerson, Nature, Boston: James Munroe and Company, 1836, pp. 76–81 (Chapter VII ‘Spirit’). Iš anglų kalbos vertė Ruslanas Baranovas, Marius Jakštas, Vaida Kalkauskaitė, Kęstas Kirtiklis, Živilė Pabijutaitė, Viktorija Ringytė, Andrius Šimašius, Vytautas Šliuburys, Vytautas Vyšniauskas